Case Report: Persistent Hypogammaglobulinemia More Than 10 Years After Rituximab Given Post-HSCT - Luterbacher, Fanny; Bernard, Fanette; Baleydier, Frédéric; Ranza, Emmanuelle; Jandus, Peter; Blanchard-Rohner, Geraldine (Frontiers in Immunology, 2021)
Rituximab (RTX) is an anti-CD20 monoclonal antibody that targets B cells—from the immature pre-B-cell stage in the bone marrow to mature circulating B cells—while preserving stem cells and plasma cells. It is used to treat autoimmune diseases, hematological malignancies, or complications after hematopoietic stem cell transplantation (HSCT). Its safety profile is acceptable; however, a subset of patients can develop persistent hypogammaglobulinemia and associated severe complications, especially in pediatric populations. We report the unrelated cases of two young men aged 17 and 22, presenting with persistent hypogammaglobulinemia more than 7 and 10 years after treatment with RTX, respectively, and administered after HSCT for hemolytic anemia and Epstein–Barr virus reactivation, respectively. Both patients’ immunological workups showed low levels of total immunoglobulin, vaccine antibodies, and class switched-memory B cells but an increase in naive B cells, which can also be observed in primary immunodeficiencies such as those making up common variable immunodeficiency. Whole exome sequencing for one of the patients failed to detect a pathogenic variant causing a Mendelian immunological disorder. Annual assessments involving interruption of immunoglobulin replacement therapy each summer failed to demonstrate the recovery of endogenous immunoglobulin production or normal numbers of class switched-memory B cells 7 and 10 years after the patients’ respective treatments with RTX. Although the factors that may lead to prolonged hypogammaglobulinemia after rituximab treatment (if necessary) remain unclear, a comprehensive immunological workup before treatment and long-term follow-up are mandatory to assess long-term complications, especially in children.